Value chain excellence – managing variability to stabilise and exploit the mine value chain. Issue 4 (1st October 2020) - Bloss, Martyn L.; Capes, Geoff W.; Seib, Russell; Alford, Liam V.; Light, Jack L.; Minniakhmetov, Ilnur; Nielsen, Chris
ABSTRACT: Mining occurs in highly variable, spatially dynamic environments. Existing methods of planning and operations management are insufficient to adequately account for variability. Managing variability within the value chain aims to maximise business value. This paper presents a methodology for managing variability. This includes: assessing the impact of variability on a deterministic mine schedule; applying guiding principles based on Theory of Constraints to stabilise and exploit the value chain; developing a risk approach to minimise costs of plan delivery; and establishing tools for critical path planning, reconciling performance against plan and establishing corrective actions to deliver plan outcomes. A case study is presented from the Olympic Dam mine. Conclusions include: operations contain significant variability that if not managed will fail to deliver the mine plan; the proposed methodology can be applied to reduce variability and robustly deliver the best-value mine plan; and this methodology has broad application across the mining industry.